DRAMATURGI TERHADAP PENGGUNA AKUN ALTER DI MEDIA SOSIAL TWITTER (FENOMENOLOGI AKUN ALTER KPOP MAHASISWA SURABAYA) (Universitas Negeri Surabaya, 2023)
This researche examines the phenomenon of second twitter accounts (alter accounts) among Surabaya students. This is how students play the second twitter account (alter account). What kind of role do they play in the front and back stages of twitter social media? The theory used in this thesis is Erving Geoffman's Dramaturgical Theory. The purpose of this thesis is to determine how the Dramaturgical phenomenon of alter K-pop accounts on twitter is played by students in Surabaya. This thesis uses a qualitative method with the data collection techniques of interviews, observations, and analysis of seven informants. The results showed that 7 (seven) informants used the second account for a variety of reasons. Five of them deliberately used a second account to show or be their other selves and